1990
DOI: 10.1073/pnas.87.11.4284
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Kirsten-ras-revertant 1 gene: potentiation of its tumor suppressor activity by specific point mutations.

Abstract: Kirsten-ras-revertant 1 (Krev-1) cDNA encodes a ras-related protein and exhibits an activity of inducing flat revertants at certain frequencies (2-5% of total transfectants) when introduced into a v-K-ras-transformed mouse NIH 3T3 cell line, DT. Toward understanding the mechanism of action of Krev-l protein, we constructed a series of point mutants of Krev-1 cDNA and tested their biological activities in DT cells and HT1080 human fibrosarcoma cells harboring the activated N-ras gene. Substitutions of the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 27 publications
5
70
0
2
Order By: Relevance
“…In those studies in which S17 mutants of Rap1A has been examined, this mutant was found to be inactive (S17D in ref. Kitayama et al, 1990; S17N in refs. Maly et al, 1994 andGabig et al, 1995), as predicted from the observed decrease in nucleotide a nity, in analogy to the Ras situation.…”
Section: Resultsmentioning
confidence: 99%
“…In those studies in which S17 mutants of Rap1A has been examined, this mutant was found to be inactive (S17D in ref. Kitayama et al, 1990; S17N in refs. Maly et al, 1994 andGabig et al, 1995), as predicted from the observed decrease in nucleotide a nity, in analogy to the Ras situation.…”
Section: Resultsmentioning
confidence: 99%
“…This antagonism has been attributed to the ability of Rap1A to form nonproductive complexes with key Ras e ectors important for Ras transforming activity. This may occur because Rap1A may bind, but fail to activate some Ras e ectors such as Raf-1 (Kitayama et al, 1989(Kitayama et al, , 1990. Alternatively, since Rap1A is located in the endoplasmic reticulum and Golgi, it may sequester Ras e ectors in a subcellular location that prevents their complete activation to or from functional signaling complexes (Beranger et al, 1991;Sato et al, 1994;Cook et al, 1993).…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 99%
“…Rheb Antagonizes Ras Signaling and TransformationSince Rheb lacked the growth promoting activity seen with constitutively activated mutants of Ras, TC21, or R-Ras, we next determined if Rheb was more similar to KRev-1/Rap1A and, instead, could antagonize Ras function (32,33). For these analyses, we used the constitutively activated KRev-1(63E) mutant as a positive control for these co-transfection focus formation inhibition assays (33).…”
Section: Aberrant Rheb Expression Does Not Alter the Growth Of Nihmentioning
confidence: 99%
“…Exceptions include TC21/R-Ras2 (10, 11), R-Ras (12,13), RhoA (14 -18), RhoB (19), and Rac1 (17,20), where constitutively activated versions of these Ras-related proteins can cause tumorigenic transformation of NIH 3T3 cells. The transforming activities of TC21 and R-Ras reflect the fact that these two Ras-related proteins share complete identity with the core Ras effector domain (Ras residues [32][33][34][35][36][37][38][39][40] and, consequently, may activate downstream signaling pathways in common with those that mediate Ras transforming potential (21). However, although the Raf-1 serine/threonine kinase is clearly a critical effector important for Ras signaling and transformation (22)(23)(24)(25)(26)(27), neither TC21 nor R-Ras cause activation of Raf-1 (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation